Crosstalk between decidual natural killer cells and extravillous trophoblasts at the maternal-fetal interface: current status and future perspectives - Qiu, Yeqi; Chen, Mingye; Lin, Rong; Chen, Xiaoyan; He, Lichun; Yin, Hui; Chen, Xian (Frontiers in Immunology, 2025)
The immune tolerance microenvironment is essential for the establishment and maintenance of pregnancy at the maternal-fetal interface. The maternal-fetal interface is a complex system containing various cells, including decidual stromal cells, lymphocytes, and trophoblasts. Decidual natural killer cells (dNKs) are the largest leukocytes and play a critical role in maintaining maternal-fetal immune tolerance and regulating the biological behaviors of extravillous trophoblasts (EVTs). Numerous studies have investigated the crosstalk between dNKs and EVTs at the maternal-fetal interface. On the one hand, dNKs can affect the invasion and migration of EVTs. On the other hand, EVTs can influence the immunological function of dNKs and the state of the maternal-fetal immune microenvironment. This review aims to summarize the most recent advancements in comprehending the phenotypes and functions of dNKs and EVTs, as well as their dynamic interactions that are crucial for the establishment and maintenance of pregnancy. Further developments in this area will greatly enhance both basic research and clinical applications in the field of reproductive medicine.